Balancing promise and concern in AI therapy: a critical perspective on early evidence from the MIT–OpenAI RCT - Ophir, Yaakov; Tikochinski, Refael; Elyoseph, Zohar; Efrati, Yaniv; Rosenberg, Hananel (Frontiers in Medicine, 2025)
The emergence of AI therapy chatbots has the potential to reduce the widening gap between the huge demand for psychological support today and the limited availability of professional care. However, some scholars and clinicians are warning that the integration of these chatbots could paradoxically lead to negative outcomes, such as dependence, loneliness, and depression. Recently, a joint research team from MIT and OpenAI conducted a four-week Randomized Controlled Trial (RCT), reporting that “while participants on average were less lonely after the study… extended daily interactions with AI chatbots can reinforce negative psychosocial outcomes”. Considering the substantial public and academic attention that followed the preprint publication of this RCT, it is crucial to examine the strength of the evidence and the validity of its interpretation before drawing firm conclusions. In this commentary, we offer a careful and appreciative review of this well-designed and timely study. Nonetheless, we argue that due to key analytical limitations, the findings do not substantiate claims of harmful effects. Given the transformative potential of AI-based interventions, we urge caution in interpreting early findings and offer practical guidance for future research.